EVALUASI SISTEM DAN PROSEDUR PENERIMAAN PENDAPATAN ASLI DAERAH (PAD) KABUPATEN NABIRE - Effendhi, Ria A.; Sondakh, Jullie J.; Budiarso, Novi S. (Universitas Sam Ratulangi, 2017)
Regional Original Revenue (PAD) is the revenue earned by the region from sources within its own area which are levied according to the local regulations in accordance with the prevailing laws and regulations. The cash receipts system and procedures used in the scope of government are one of the most important parts in implementing local financial management, in an effort to increase the local revenue (PAD). The analytical method used is descriptive analysis, while evaluation of system and procedure is done by comparing between the concepts, theories and the rules in the implementation of the system and the procedure of receipt of PAD, especially with the provision of PERMENDAGRI No. 59. Based on this research, it is found that the acceptance system and procedures at the Nabire Regency Revenue Service have been conducted in accordance with Law No. 16 of 2000 and PERMENDAGRI No. 59 Year 2007. Keywords:Â Systems and Procedures Receipts